The method of lithological dissection and mapping of near-surface deposits based on the assessment of differences in gamma‒radiation energy (Proceedings of Voronezh State University. Series: Geology, 2023)
The results of field experiments on the study of the possibility of using the differences of rocks in the energy of gamma radiation to develop a method for mapping the lithological heterogeneity of soil massifs and identifying disturbed zones in them are presented. When using the radiometer-dosimeter RKS-107 in experiments, it was found that in the third operating mode with the detector lid closed, when measuring from the soil surface under the same conditions, the gamma radiation energy is recorded in this way in values with less variability than in the measurement modes of other radiation field parameters. The influence of various factors (soil and snow cover, seasonal conditions, air temperature, different gamma activity and thickness of underlying and overlapping rocks) on the variability of gamma radiation energy values has been studied. It is shown that these conditions are not limiting for the application of this method of assessing the radioactive properties of rocks as an auxiliary method in landscape, engineering-geological, engineering-ecological mapping. It is shown that petrochemical varieties of rocks have stable and narrow ranges of gamma radiation energy. For terrigenous autochthonous deposits, this range is determined by the ratio of detrital quartz and clay matrix.
Keywords: lithological mapping; radiological methods; radiometer-dosimeter; gamma radiation energy; disturbed zones; engineering surveys